2022
DOI: 10.1007/s11042-022-13370-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of augmented reality on foreign language teaching: a case study of Persian language

Abstract: The use of information technology in the field of foreign language teaching as an auxiliary tool is very important. In a foreign language classroom, place is just an abstract concept; where the language is separated from the community, culture and places in which it is used. Augmented reality is a technology in which virtual components are simultaneously combined with the real environment. Our aim in this study is to investigate the effects of location-based augmented reality in teaching Persian as a foreign l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This study confirms that the "Mandarin AR" app is highly beneficial in enhancing non-native speakers' Mandarin vocabulary development. This is consistent with previous studies which demonstrated that the AR technology has positive impacts on language learning by creating immersive and personalized language learning experiences, boosting students' motivation and increasing learning retention in the mind (Belda-Medina & Marrahi-Gomez 2023; Kazu & Kuvvetli, 2023;Mozaffari & Hamidi 2023;Shadiev & Liang 2023). Several reasons may be accounted for the significant achievement in this study.…”
Section: Discussionsupporting
confidence: 92%
“…This study confirms that the "Mandarin AR" app is highly beneficial in enhancing non-native speakers' Mandarin vocabulary development. This is consistent with previous studies which demonstrated that the AR technology has positive impacts on language learning by creating immersive and personalized language learning experiences, boosting students' motivation and increasing learning retention in the mind (Belda-Medina & Marrahi-Gomez 2023; Kazu & Kuvvetli, 2023;Mozaffari & Hamidi 2023;Shadiev & Liang 2023). Several reasons may be accounted for the significant achievement in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the use of AR tools can also make a difference in the learner's emotions. On the one hand, it can improve students' positive emotions, such as satisfaction, enthusiasm, interaction with the environment and people, motivation, and positive perceptions of augmented reality use, making learning more effective [21,45]. On the other hand, it can also reduce learners' anxiety, increase their creativity, and foster their cooperation [39,47].…”
Section: Resultsmentioning
confidence: 99%
“…AR is a real-time representation using computer-generated images, sounds, or videos that allows users to interact with the real world in an augmented way [10]. As an assistant tool, the application of this technology is very important in language teaching and learning [21] because mobile applications for touch screens can offer children new opportunities for language learning [22]. However, foreign language teaching is difficult and needs effective skills to avoid boredom.…”
Section: Ar In Language Learningmentioning
confidence: 99%
“…Marker-based tracking, which includes image markers and 2D barcodes, is a reliable and cheap approach for creating AR applications (Santos et al, 2016). Among the ten studies using markerless tracking (25%), six relied on location-based technologies such as GPS for outdoor activities with location-relevant content (Liu et al, 2016;2018;Ho et al, 2017;Perry, 2021;Lee, 2022;Mozaffari and Hamidi, 2023).…”
Section: Type Of Markers [Rq1]mentioning
confidence: 99%
“…Game-based approaches, for example, offer a collaborative and contextual learning experience (Taskiran, 2019). Gamified learning and lessons outside the classroom are strengths of AR, which benefit understanding of taught concepts and allow students to practice the target language in a realistic environment with authentic communication (Mozaffari and Hamidi, 2023).…”
Section: Type Of Markers [Rq1]mentioning
confidence: 99%